2012
DOI: 10.1115/1.4007322
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Design Performance of the Semi-Closed Oxy-Fuel Combustion Combined Cycle

Abstract: This study aims to present various design aspects and realizable performance of the natural gas fired semi-closed oxy-fuel combustion combined cycle (SCOC-CC). The design parameters of the cycle are set up on the basis of the component technologies of today's state-ofthe-art gas turbines with a turbine inlet temperature between 1400°C and 1600°C. The most important part of the cycle analysis is the turbine cooling, which considerably affects the cycle performance. A thermodyruxmic cooling model is introduced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 18 publications
2
9
0
Order By: Relevance
“…This can partly explain that only some of the studies aimed at optimizing the cycle with respect to pressure ratio, while others only selected a pressure ratio based on, for example, experience. Corchero et al [14] and Yang et al [16] looked at different pressure ratios and show similar trends as has been found in the current study. The resulting efficiencies from these studies have a very large spread and ranges from 36.7% to 53.9%.…”
Section: Scoc-ccsupporting
confidence: 89%
See 1 more Smart Citation
“…This can partly explain that only some of the studies aimed at optimizing the cycle with respect to pressure ratio, while others only selected a pressure ratio based on, for example, experience. Corchero et al [14] and Yang et al [16] looked at different pressure ratios and show similar trends as has been found in the current study. The resulting efficiencies from these studies have a very large spread and ranges from 36.7% to 53.9%.…”
Section: Scoc-ccsupporting
confidence: 89%
“…Corchero et al did a parametric study with regard to the pressure ratio at a fixed turbine entry temperature of 1327 ∘ C [14]. Yang et al [16] modelled the SOCC-CC along with the ASU and the CO 2 compression train at different pressure ratios and two different turbine inlet temperatures, 1200 ∘ C and 1600 ∘ C. They concluded that the optimal pressure ratio is around 60 and 90 for the turbine inlet temperatures of 1418 ∘ C and 1600 ∘ C, respectively. With optimal design conditions, the net cycle efficiency is lower than the efficiency of the conventional CC by about 8 percentage points for both of the two turbine inlet temperatures.…”
Section: Scoc-ccmentioning
confidence: 99%
“…*this value is attributed by independent researchers [52] which lies between the one provided by the company [9] and Llorente [38], 58.9 and 51.9%, respectively. **this value approximates efficiencies presented in other studies [53,54] The economic data provided for each cycle have different assumptions depending on factors such as the power plant size, the fuel price, the discount rate, etc. Thus, in order to show the results and make them comparable, the costs for each cycle have been divided by the costs for its reference plant (CCGT), obtaining a ratio that represents their overcost.…”
Section: Economicsupporting
confidence: 77%
“…Recently, alternative thermodynamic cycles are actively investigated, permitting, without significant energy costs, to remove CO 2 , formed as a result of fuel combustion [1][2][3][4], from the cycle. Calculations have shown that such cycles may not be inferior to the most advanced power plants with regard to thermal efficiency [4].…”
Section: Introductionmentioning
confidence: 99%